Liberalism And The Question Of Escalation From The Great Rejection To The One-dimensional Resistance By Herbert Marcuse - A Critical Inquiry By Herbert Marcuse - abdelkrim, fadhila; Bensmaine, moussa (El Omda in Linguistics and Discourse Analysis, 2025)
This research paper deals with the questioning of liberalism and what surrounds it in terms of what has been accomplished in the lives of individuals, that are cut off from all links with the human world and does not achieve that desired approach to find out about the problems of liberal thought and its applications. and this is what actually happens in societies. Which made liberalism a living model for its political and economic issues, and it is an attempt to support the transition from understanding reality to changing it according to Harbert Marcuse’s view, which he called the concept of the great refusal to resist the one dimension that liberalism produced with all its stations that were renewing its intellectual load from time to time to make it possible And accompanying social and historical changes.